Hubungan Budaya Nelayan Terhadap Perekonomian dan Ekosistem Laut di Pantai Labu Kecamatan Paluh Sibaji - Seftyani, Ade Irma; Araafi, Alif; Muharani, Anisa; Ariyansyah, Fauzy; Oktapiani, Friska Dela; Ardila, Maisyah; Andaresta, Novi; Raspiyahni, Raspiyahni; Pasaribu, Syahril Budiman; Nasution, Ummi Kalsum; Ayu, Delfriana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Indonesia is a country known for its cultural diversity, more than that Indonesia also has a very wide water area. Most of Indonesia's territory consists of oceans and has considerable marine potential. With the potential it has, it should be able to prosper the community, fishermen who depend on this marine (maritime) potential. But in reality, the life of fishing communities is always poverty stricken, even the life of fishermen is often identified with poverty. Fishermen (especially labor fishermen and traditional fishermen) are part of a community group that can be classified as the poorest social layer among coastal community groups. This research method uses a qualitative descriptive research design. The population in this study were all fishermen in the coastal area of ​​Pantai Labu, Palu Sibaji District. Sampling of this study by accidental sampling. Data collection techniques in research by way of interviews using prepared questionnaires. Respondents in this study amounted to 30 people who work as fishermen. The findings from this study, most of the fishermen still catch fish using traditional tools, besides that the fishermen also make efforts to protect aquatic ecosystems such as making fish houses and strictly prohibiting the occurrence of sea bombings. Keywords: Fisherman's culture, marine ecosystem, economy